2018
DOI: 10.1016/j.jmii.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cervical colonization by Ureaplasma parvum, Ureaplasma urealyticum , Mycoplasma hominis and Mycoplasma genitalium in childbearing age women by a commercially available multiplex real-time PCR: An Italian observational multicentre study

Abstract: multiplex RT-PCR can be a valuable tool to evaluate the real epidemiology of cervical mycoplasma colonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
3
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 29 publications
5
49
3
5
Order By: Relevance
“…A study conducted in Japan showed an Ureaplasma parvum prevalence of 41.7% in women attending their first prenatal visit [23]; another study, carried out in Slovenia, showed that significantly more women aged 25 years and younger were infected with U. urealyticum (23.4%) compared to those aged above 25 years (9.2%), irrespective of symptoms [28]. Other studies conducted in Italy have reported positivity rates for Ureaplasma parvum of almost 25% in vaginal specimens [22] and 38.3% in cervical samples [29].…”
Section: Discussionmentioning
confidence: 97%
“…A study conducted in Japan showed an Ureaplasma parvum prevalence of 41.7% in women attending their first prenatal visit [23]; another study, carried out in Slovenia, showed that significantly more women aged 25 years and younger were infected with U. urealyticum (23.4%) compared to those aged above 25 years (9.2%), irrespective of symptoms [28]. Other studies conducted in Italy have reported positivity rates for Ureaplasma parvum of almost 25% in vaginal specimens [22] and 38.3% in cervical samples [29].…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of M. hominis , U. urealyticum and U. parvum in non‐pregnant sexually active symptomatic and asymptomatic women, measured by molecular tests including species differentiation, has ranged between 3.1–15% #bib5.2–20% and 20–89%, respectively . The large variation in prevalence probably reflects both methodological and true population differences, in particular in the prevalence of BV, the most important confounder.…”
Section: Womenmentioning
confidence: 99%
“…However, both of these ureaplasmas are frequently associated with increased positivity for several traditional STIs, e.g. C. trachomatis and M. genitalium , and/or BV . The bacterial load of particularly M. hominis and to a lesser extent U. parvum and U. urealyticum can be significantly increased in the dysbiosis of BV .…”
Section: Womenmentioning
confidence: 99%
See 2 more Smart Citations